1, 2‐Difunctionalization of Acetylene Enabled by Light. (13th March 2023) - Lü, Shiwei; Wang, Zipeng; Gao, Xiang; Chen, Kai; Zhu, Shifa
Abstract: Although the direct conversion of gaseous acetylene into value‐added liquid commodity chemicals is becoming increasingly attractive, the majority of the established methodologies are focused on cross‐coupling, hydro‐functionalization, and polymerization. Herein, we describe a 1, 2‐difunctionalization method that inserts acetylene directly into readily available bifunctional reagents. This method provides access to diverse C2‐linked 1, 2‐bis‐heteroatom products in high regio‐ and stereoselectivity along with opening up previously unexplored synthetic directions. In addition, we demonstrate this method's synthetic potential by converting the obtained products into diverse functionalized molecules and chiral sulfoxide‐containing bidentate ligands. Using a combination of experimental and theoretical methods, the mechanism for this insertion reaction was investigated. Abstract : Reported is the regio‐ and stereoselective light‐enabled installation of two distinct sulfides into acetylene. The resulting S‐containing vinyl frameworks are important and versatile scaffolds that can be easily transformed into diverse functionalized molecules and chiral sulfoxide‐containing bidentate ligands. Experimental and theoretical data on the mechanism are reported.